Aedes albopictus Strain and Dengue Virus Serotype in the Dengue Fever Outbreaks in Japan: Implications of Wolbachia Infection - Sasaki, Toshinori; Moi, Meng Ling; Saito, Kazumi; Isawa, Haruhiko; Takasaki, Tomohiko; Sawabe, Kyoko (Japanese Journal of Infectious Diseases, 2022)
From August 27 to October 15, 2014, a dengue fever outbreak with 158 autochthonous cases occurred after nearly 70 years of no reports of autochthonous cases in Japan. The most competent mosquito vector for dengue virus (DENV) transmission in Japan is Aedes albopictus. Since A. albopictus is widely distributed throughout Japan, we examined the susceptibility of this species to infection by DENV and the relationship of the endosymbiont Wolbachia (wAlbA and wAlbB) with susceptibility to DENV. The A. albopictus YYG strain, collected from the Yoyogi Park in 2014, the epicenter of the dengue fever outbreak, was found to have lower susceptibility to DENV 1 and 3 than that of the indigenous Japanese strains A. albopictus EBN 201808 (F1 from the field) and A. albopictus ISG 201603. Furthermore, the A. albopictus EBN 201808 strain showed the same susceptibility to DENV3 as the A. albopictus ISG 201603tet strain (Wolbachia-free). Susceptibility to DENV3 was not related to Wolbachia strains wAlbA or wAlbB in the A. albopictus ISG 201603 strain.